Pelatihan Penulisan Comprehension Questions Berorientasi High-Order Thinking Skills Bagi Guru Bahasa Inggris SMP di Kabupaten Lombok Barat - Thohir, Lalu; Soepriyanti, Henny; Amin, Muhammad; Isnaini, Mh. (Jurnal Gema Ngabdi, 2024)
In learning, a teacher needs to train his students to think critically so that they can make the right decisions when solving a problem. For this purpose, teachers can take advantage of question-and-answer activities by asking questions or questions in the HOTS (High Order Thinking Skills) category. This Community Service (PKM) activity aims to provide training for teachers so that they can improve their skills in preparing questions (comprehension questions) that are oriented towards critical thinking abilities. This PKM activity was carried out at SMPN 4 Narmada involving 22 English teachers who were members of the English Middle School MGMP in West Lombok district. This PKM activity takes the form of training or technical guidance in preparing questions which begins with presentation of material, questions and answers, group work, presentation of group work results, and evaluation or providing feedback. The results of this PKM activity show that the teachers were very enthusiastic in participating in the series of activities, especially when preparing questions in groups, presenting the results of group work and discussions. The questions produced by participants in groups show a focus not only on low-level thinking abilities but also on high-level thinking abilities. From the results of the existing questionnaire, in general the teachers stated that they welcomed this activity and hoped that there would be similar activities that could improve their competence as English teachers. Keywords: Comprehension Questions; HOTS; English Teacher